A Guide to the Description of Architectural Drawings - J. Paul Getty Trust (2005)
[Dt.:] Die Website des Getty Institute gibt einen Leitfaden für die Beschreibung von Architekturzeichnungen. Die für eine vollständige Katalogisierung notwendigen Metadaten werden genannt und erörtert. - [Engl.:] Guidelines, conventions, and standards for describing architectural drawings and documents, with examples and recommendations for authority files and controlled vocabularies